Safety and efficacy of endovenous laser therapy with microphlebectomy or foam sclerotherapy for varicose vein patients in outpatient clinic - Saadoon Hamad Al Hayazie; Abdulameer Mohsin Hussein (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Varicose vein of the lower extremity are common problems which is commonly the result of reflux in one or more of the saphenous veins and their primary tributaries. The new treatment modalities including endovenous laser therapy for truncal refluxing vein with microphebectomy or foam sclerotherapy for tributeries are highly effective and safe in outpatient clinic.Method:From Jan , 2015, to Jan , 2022, 1500 EVLT procedures were performed in 1500 patients with a mean age of 42.6 years (range, 15-75 years). A 1470-nm diode laser (Venacure laser device ,Angiodynamics and Wolf device by ARC Laser ) and microphlebectomy or foam sclerotherapy were used for tributaries and perforators. All refluxing truncal veins above knee were ablated . Symptoms of venous insufficiency were present in 67%, and 90 patients (2.85%) had an open ulcer when they underwent operation. Patients had clinical follow-up visits, including duplex ultrasound examination, at 1 week, 1 month, 3 months ,6 months and were assessed for deep venous thrombosis (DVT), recanalization of the ablated vein, nerve injury, ulcer healing, and resolution of symptoms.Results:A total of 1300 great saphenous veins (86.66%), 120 small saphenous veins (8%), 42 combined great and short saphenous veins (2.8) were ablated by endovenous laser therapy . Combined microphlebectomies or foam sclerotherapy were performed at the same session . The primary ablation rate at 1 and 6 months was 99.2% . Recanalization occurred in 12 veins (0.85%) who successfully closed with a second EVLT. Postoperatively, the 90 ulcers showed healing at a mean of 5.2 weeks (range, 2-10 weeks), and only 1 failure of healing . a few major complications occurred. 6 cases of DVT (0.28%) occurred, 10 mild pulmonary emboli ,one (0.28%) skin burns had occurred. Local transient paresthesia at the ankle and midcalf level occurred in 9 patients (0.6 %).Conclusions:Endovenous laser therapy for superfacial refluxing truncal veins together with microphlebectomy or foam sclerotherapy for tributeries highly effective and safe in treating varicose vein in an outpatient clinic.